Equity in recruitment to Combined Infection Training, 2021: Diversity & Inclusion considerations. Issue 4 (October 2022) - Aggarwal, Dinesh; Roy-Chowdhury, Meera; Xiang, Nicola; Peacock, Sharon J.
Highlights: First insights into Diversity and Inclusion data on Combined Infection Training recruitment. Recruitment to infection specialities appears Gender balanced. Disparities in recruitment by Ethnicity appear to be explained by UK versus Non-UK graduate status. Further work is required to evaluate pay gaps, progression and retention by protected characteristics within infection specialities.